Money Market Instruments and Economic Growth in Nigeria (Lapai Journal of Economics, 2023)
Effect of money market instruments on economic growth of Nigeria from 1993 to 2022 was investigated in this study. Research design adopted for this study is ex-post-facto. Data were obtained from Central Bank of Nigeria (CBN) Statistical Bulletin to estimate the model. Multiple regression approach was employed to analyse impact of money market instruments on economic growth in Nigeria for the period of the study. From the empirical result obtained, the study conclude that money market enhanced development in Nigeria. It is recommended that CBN create appropriate monetary and fiscal measures which would develop money market for promotion of productive activities and investment thereby improve Nigeria development.